Perancangan Aplikasi Augmented Reality Statis Sebagai Media Pembelajaran Bagian Tumbuhan Hermafrodit Untuk Siswa Sekolah Dasar - Rivan Rubenzky; Munjiat Setiani Asih (Universitas Harapan Medan, 2025)
Science learning in elementary schools still often uses conventional media such as textbooks, lectures, and two-dimensional images. This condition can make it difficult for students to understand materials that require clear visual representation, such as the parts of hermaphroditic plants. This study aims to design and develop a static Augmented Reality (AR) application based on Android as an interactive learning medium for introducing the parts of hermaphroditic plants to elementary school students. The development method used in this study is the Luther multimedia development method, which consists of concept, design, material collecting, assembly, testing, and distribution stages. The application was developed using Unity 3D and Vuforia SDK with a marker-based tracking method. The 3D objects used in this application are lily and tulip flowers. The results of this study show that the application can display 3D objects of hermaphroditic plants when the smartphone camera is directed at the marker. The application also provides information menus and quiz features to support the learning process. Based on the results, this application can be used as an alternative learning medium that is more visual, interactive, and easy to use in helping elementary school students understand the parts of hermaphroditic plants.